Impact of Long-Term Proton Pump Inhibitor Use on Sexual Hormone Profiles and Sexual Function in Male Patients: A Cross-Sectional Study at CMH Rawalpindi - Sultan, Ayesha; Rehman , Fawad; Ahmad Siddiqi, Fuad; Khan , Javed Ahmad (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess the frequency of hormonal imbalances and their connection with sexual dysfunction in male patients taking proton pump inhibitors for at least three months. Study Design: Cross-sectional study Place and Duration of Study: Conducted in an Outpatient Endocrinology Clinic at CMH Rawalpindi, Pakistan from Feb to Apr 2024. Methodology: A group of 150 male patients who had been taking proton pump inhibitors regularly for three months or more were included in the study. Participants were evaluated for sexual complaints, and serum levels of prolactin, sex hormone-binding globulins, total testosterone, and progesterone were recorded. Statistical analysis was done to identify significant differences and correlations between hormonal levels and sexual dysfunction symptoms. Results: Among the 150 participants, 90 reported sexual complaints, while 60 did not. Patients with sexual complaints had significantly different mean serum levels of prolactin (p<0.001), sex hormone-binding globulins (p=0.043), total testosterone (p<0.001), and progesterone (p=0.001) compared to those without sexual complaints. Higher prolactin levels were noted in patients with sexual complaints (p<0.001). Significant correlations were found between serum prolactin levels and sex hormone-binding globulins (p=0.003), total testosterone (p=0.008), and progesterone (p<0.001). Symptoms such as decreased libido (p=0.001), erectile dysfunction (p=0.001), and decreased semen volume (p<0.001) showed significant variation between normal and hyperprolactinemic patients. Conclusion: Long-term use of proton pump inhibitors in male patients is linked with significant hormonal imbalances that may contribute to sexual dysfunction. Monitoring and managing these hormonal changes are essential for improving the quality of life in affected patients.